The Use of Young Coconut Water in Pediatric Cholera - Harun Nurasid; Teddy Ontoseno; Subijanto Purwodibroto (Paediatrica Indonesiana, 1979)
Eighty-stx children suffering from cholera, aged 2 - 12 years, admitted to the Dr. Sutomo Hospital, Surabaya, were treated intravenously with Ringer Lactate as initial rehydration. Concomitantly young coconut water was given orally ad libitum until complete rehydration was achieved.